2022
DOI: 10.3389/fpls.2021.715730
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Abiotic Stressors Drive Grassland Community Assembly of Tibet and Mongolia Plateau

Abstract: Multiple ecological processes simultaneously govern community assembly, but it remains unclear how abiotic stressors regulate the relative importance of these processes among different biogeographic regions. Therefore, we conducted a comprehensive study on the responses of community assembly to varying environmental gradients, using the mean, variance, skewness, and kurtosis of plant height (height), specific leaf area (SLA) and leaf dry matter content (LDMC) distributions on the Tibetan Plateau (TP) and the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
2
5
0
Order By: Relevance
“…Stress-dominance hypothesis believes that abiotic filtering would dominate community assembly and leads to functional phylogenetic convergence in a more stressful habitat, while biotic interaction, such as competition exclusion, plays a major role and resulting in divergence in a more favorable environment (Schöb et al, 2013 ; Coyle et al, 2014 ). In this study, we observed that most traits, as well as all the traits combined exhibited functional convergence, consistent with the findings of Chinese grasslands (Wang et al, 2021a ). This may suggest that abiotic filtering drives the Gobi plant community's functional structure.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Stress-dominance hypothesis believes that abiotic filtering would dominate community assembly and leads to functional phylogenetic convergence in a more stressful habitat, while biotic interaction, such as competition exclusion, plays a major role and resulting in divergence in a more favorable environment (Schöb et al, 2013 ; Coyle et al, 2014 ). In this study, we observed that most traits, as well as all the traits combined exhibited functional convergence, consistent with the findings of Chinese grasslands (Wang et al, 2021a ). This may suggest that abiotic filtering drives the Gobi plant community's functional structure.…”
Section: Discussionsupporting
confidence: 91%
“…However, plant functional and phylogenetic distributions were driven by a wide range of environmental factor (López-Angulo et al, 2018 ; Backhaus et al, 2021 ; Catano et al, 2021 ). For example, trait convergence was mainly driven by temperature on the Tibet Plateau, whereas water availability governs trait convergence on Mongolian Plateau (Wang et al, 2021a ). This study found that the distribution patterns of phylogeny and most traits were mainly influenced by local habitat factors, such as gravel coverage and soil condition, rather than climate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations